2022
DOI: 10.1088/1361-6528/ac55d1
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials enhancing the solid-state storage and decomposition of ammonia

Abstract: Hydrogen is ideal for producing carbon-free and clean-green energy with which to save the world from climate change. Proton exchange membrane fuel cells use to hydrogen to produce 100% clean energy, with water the only by-product. Apart from generating electricity, hydrogen plays a crucial role in hydrogen-powered vehicles. Unfortunately, the practical uses of hydrogen energy face many technical and safety barriers. Research into hydrogen generation and storage and reversibility transportation are still in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 76 publications
0
0
0
Order By: Relevance
“…At present, HEAs-related catalytic reactions can be mainly divided into two categories, one is thermal-driven catalysis, which includes ammonia decomposition reactions, ethanol oxidation reactions, methanol oxidation reactions, CO oxidation reactions, and the other is electrocatalysis, which mainly includes hydrogen evolution reaction (HER), oxygen evolution reaction (OER), carbon dioxide reduction reaction (CO 2 RR) and so on [60]. Next, we will introduce the application of HEAs in these reactions in detail.…”
Section: Application Of Heas In Catalytic Reactionsmentioning
confidence: 99%
“…At present, HEAs-related catalytic reactions can be mainly divided into two categories, one is thermal-driven catalysis, which includes ammonia decomposition reactions, ethanol oxidation reactions, methanol oxidation reactions, CO oxidation reactions, and the other is electrocatalysis, which mainly includes hydrogen evolution reaction (HER), oxygen evolution reaction (OER), carbon dioxide reduction reaction (CO 2 RR) and so on [60]. Next, we will introduce the application of HEAs in these reactions in detail.…”
Section: Application Of Heas In Catalytic Reactionsmentioning
confidence: 99%
“…Most of the investigations that aim to generate H 2 from NH 3 decomposition are performed at elevated temperatures [14,15,31]. However, the application of NH 3 as a hydrogen carrier requires in situ production at suitable reaction conditions (temperatures and pressures) to be used in fuel cells.…”
Section: Catalytic Thermal Decomposition Of Nhmentioning
confidence: 99%
“…Therefore, a high surface area is usually thought to be a positive factor for dispersing metals, resulting in a larger number of active sites and assisting the mass transfer of the reaction [14,31,34,55,76,94]. In contrast, it is found that the utilization of precursors, mainly perovskites or hydrotalcites, could help to control the metal size to be small, providing high dispersion.…”
Section: Bimetallic Catalysts and Metal Catalystsmentioning
confidence: 99%